ANALISIS KORELASI KINERJA PELAKSANAAN TERHADAP KUALIFIKASI KONTRAKTOR PADA PROYEK KONSTRUKSI DI KOTA PALANGKA RAYA - Sjaiful Bahri (INFO-TEKNIK, 2014)
This study directly measure the quality of small contractors primarily improve the ability of small contractors in project management. Quality contractors in the implementation of the project can be seen that the performance has been achieved in implementing the project contractor. Analysis of performance measurement is done by looking at what has been done in accordance with the scope of the contractor and the quality preset with the number of resources that have been used.The method used in this research is to analyze the performance of executing the qualifications of the contractor at the Department of Public Works Palangkaraya. Background qualified contractor also has a close connection with financial, Human-resources, equipment and experience of the company that created the data in the table is the result of the questionnaire. Data analysis technique is used to measure the relative correlation of each factor research (performance execution) with the classification of contractors, so it can be categorized based on the level of relationship resulting correlation coefficient.The results showed that the correlation coefficient with the category of relationship factors Very Tinggidihasilkan Financial settings (Cash Flow) the Contractor Qualifications, that is equal to 0.810. High correlation coefficients with the category resulting from the relationship between achievement of objective (0.759), Order Administration factor (0.754),, factors Coordination and Integration (0.596), and the factor of Control Engineering Construction (.663) with Contractor Qualification. While the correlation coefficient with the Medium category resulting from the relationship factor Implementation Method (0.540), Communications factor (0.403), Coordination and Integration factor (0.596), and the factor of Security and Safety (0,579). Keywords: correlation, performance implementation, the classification of contractor